Broad impact of deleting endogenous cannabinoid hydrolyzing enzymes and the CB1 cannabinoid receptor on the endogenous cannabinoid-related lipidome in eight regions of the mouse brain. (August 2016) - Leishman, Emma; Cornett, Ben; Spork, Karl; Straiker, Alex; Mackie, Ken; Bradshaw, Heather B.
Graphical abstract: Abstract: Background and purpose: The enzymes fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL) hydrolyze endogenous cannabinoids (eCBs), N -arachidonoyl ethanolamine (AEA) and 2-arachidonoyl glycerol (2-AG), respectively. These enzymes also metabolize eCB analogs such as lipoamines and 2-acyl glycerols, most of which are not ligands at CB1 . To test the hypothesis that deleting eCB hydrolyzing enzymes and CB1 shifts lipid metabolism more broadly and impacts more families of eCB structural analogs, targeted lipidomics analyses were performed on FAAH KO, MAGL KO, and CB1 KO mice and compared to WT controls in 8 brain regions. Experimental approach: Methanolic extracts of discrete brain regions (brainstem, cerebellum, cortex, hippocampus, hypothalamus, midbrain, striatum and thalamus) were partially purified on C-18 solid-phase extraction columns. Over 70 lipids per sample were then analyzed with HPLC/MS/MS. Key results: AEA and 2-AG were unaffected throughout the brain in CB1 KO mice; however, there was an increase in the arachidonic acid (AA) metabolite, PGE2 in the majority of brain areas. By contrast, PGE2 and AA levels were significantly reduced throughout the brain in the MAGL KO corresponding to significant increases in 2-AG. No changes in AA or PGE2 were seen throughout in the FAAH KO brain, despite significant increases in AEA, suggesting AA liberated by FAAH does not contribute to steady state levels of AA or PGE2 . Changes in the lipidome were not confined to the AA derivatives and showed regional variation in each of the eCB KO models. Conclusions and implications: AEA and 2-AG hydrolyzing enzymes and the CB1 receptor link the eCB system to broader lipid signaling networks in contrasting ways, potentially altering neurotransmission and behavior independently of cannabinoid receptor signaling.